A new topographic survey of the walls of Pompeii: Porta Nola from 3D laser scanner to conservation problems - Luana Toniolo; Silvia Bergami; Michele Silani (Groma, 2020)
Since 2016, within a broad collaboration agreement between the Archaeological Park of Pompeii and the University of Bologna, a new scientific research project started, with the aim to study and document the north-east sector of the walls of Pompeii, included between Porta Vesuvio and Porta Sarno. The first accomplished result was to achieve a new documentation using protocols and procedures inspired by those used by the Plan of Knowledge of the Great Pompeii Project. Within the new research, while complying with the original guidelines, we tried to update some procedures regarding the analysis of the deterioration and to propose new research lines. The works are ongoing thus we present here the first remarks and an illustrative case focused on the context of Porta Nola.